Ultrasound-guided biopsy of transplanted pancreas: evaluation of 20 cases - Marcel Vieira da Nóbrega; Carlos Leite Macedo Filho; Rodrigo Gobbo Garcia; Guilherme Falleiros Mendes; Juliano Ribeiro de Andrade; Miguel José Francisco Neto; Marcelo Buarque de Gusmão Funari (Einstein (São Paulo), 2009)
Objective: To report the experience with percutaneous biopsies of pancreatic grafts guided by ultrasonography. Methods: Series of cases referred from outpatient’s clinic for biopsy of pancreas transplant, between December 2006 and March 2008. Data were collected from medical electronic records for age, sex and histopathology. The indication for the procedure was obtained from medical and laboratory records. Doppler ultrasonography was performed for control and to guide biopsy in real time. Rresults: Twenty patients referred for biopsy of their transplanted pancreas over a one-year period were evaluated. In one patient, biopsy was not performed for having no safe access for ultrasound. It was used 18 gauge needles, mostly automatic-cut type. The main indications were increased blood glucose and pancreatic enzyme levels as well as reduction of urinary amylase. The sonographic aspect of the pancreatic graft was normal in 18 cases. In all 19 biopsies performed, satisfactory samples for histopathological study were obtained. There were no complications. Cconclusions: This series of cases demonstrated low sensitivity and specificity of ultrasound in diagnosis of pancreatic transplants disorders, but showed to be very useful to guide transplanted pancreas biopsies. Although no complications occurred in this experience, the risk-benefit relation should always be assessed for every patient.